Extracorporeal cardiopulmonary resuscitation for cardiac arrest. Issue 3 (June 2020) - Kalra, Rajat; Kosmopoulos, Marinos; Goslar, Tomaz; Raveendran, Ganesh; Bartos, Jason A.; Yannopoulos, Demetris
Abstract : Purpose of review: Extracorporeal cardiopulmonary resuscitation (ECPR) is a contemporary resuscitation approach that employs veno-arterial extracorporeal membrane oxygenation (VA-ECMO). This approach is increasingly used worldwide to mitigate the widespread hemodynamic and multiorgan dysfunction that accompanies cardiac arrest. Recent findings: In this review, the physiology of VA-ECMO and ECPR, the role of ECPR in contemporary resuscitation care, the complications associated with ECPR and VA-ECMO usage, and intensive care considerations for this population are discussed. Summary: ECPR offers a promising mechanism to mitigate multiorgan injury and allow time for the institution of supportive interventions required to effectively treat cardiac arrest. More prospective data in the context of extensive prehospital and hospital collaboration is needed to promote its successful use.